Comparisonal Analysis of Netflix and Viu Service Quality Using Servqual Method - Arvianda Iswandari; Dina Indarti (Journal of Social Research, 2022)
Background: The COVID-19 pandemic that is currently engulfing the world, governments in various countries urge people to stay at home, making VoD (Video on Demand) streaming activities as an alternative entertainment for most people experience an increase. Objective: The purpose of this research is to perform a comparative analysis of service quality on two VoD platforms, namely Netflix and Viu using the Servqual (Service Quality) method. Methods: The research was conducted by distributing questionnaires through online media to 157 Netflix and Viu users. Service quality in this study was measured using the Servqual method consisting of Tangible, Reliability, Responsiveness. Results: The results showed that IndiHome customers were not satisfied with the quality of services provided with an average gap of 1,539 (Ulkhaq and Barus, 2017). Conslusion: Based on the results of this study, it can be concluded that the average gap between reality and expectations on Netflix service quality is 0.41 while the average gap between reality and Viu's expectations is 0.24, in addition, based on the results of hypothesis testing, it proves that the significance value (sig-2 tailed ) of 0.132 and 0.134 for the perception variable. At the 5% significance level, this value is significant because the significance of 0.132 and 0.134 > 0.05 shows that there is no difference in service quality between Netflix and Viu